Regenerative Injections Including 5% Dextrose and Platelet-Rich Plasma for the Treatment of Carpal Tunnel Syndrome: A Systematic Review and Network Meta-Analysis - Chih-Peng Lin; Ke-Vin Chang; Yi-Kai Huang; Wei-Ting Wu; Levent Özçakar (MDPI AG, 2020)
This network meta-analysis aimed to integrate the available direct and indirect evidence on regenerative injections—including 5% dextrose (D5W) and platelet-rich plasma (PRP)—for the treatment of carpal tunnel syndrome (CTS). Literature reports comparing D5W and PRP injections with non-surgical managements of CTS were systematically reviewed. The main outcome was the standardized mean difference (SMD) of the symptom severity and functional status scales of the Boston Carpal Tunnel Syndrome Questionnaire at three months after injections. Ranking probabilities of the SMD of each treatment were acquired by using simulation. Ten studies with 497 patients and comparing five treatments (D5W, PRP, splinting, corticosteroid, and normal saline) were included. The results of the simulation of rank probabilities showed that D5W injection was likely to be the best treatment, followed by PRP injection, in terms of clinical effectiveness in providing symptom relief. With respect to functional improvement, splinting ranked higher than PRP and D5W injections. Lastly, corticosteroid and saline injections were consistently ranked fourth and fifth in terms of therapeutic effects on symptom severity and functional status. D5W and PRP injections are more effective than splinting and corticosteroid or saline injection for relieving the symptoms of CTS. Compared with splinting, D5W and PRP injections do not provide better functional recovery. More studies investigating the long-term effectiveness of regenerative injections in CTS are needed in the future.